Effect of climate warming on the timing of autumn leaf senescence reverses after the summer solstice - Zohner, Constantin M; Mirzagholi, Leila; Renner, Susanne S; Mo, Lidong; Rebindaine, Dominic; Bucher, Raymo; Palouš, Daniel; Vitasse, Yann; Fu, Yongshuo H; Stocker, Benjamin D; Crowther, Thomas W (Science (New York, N.Y.), 2023)
Climate change is shifting the growing seasons of plants, affecting species performance and biogeochemical cycles. Yet how the timing of autumn leaf senescence in Northern Hemisphere forests will change remains uncertain. Using satellite, ground, carbon flux, and experimental data, we show that early-season and late-season warming have opposite effects on leaf senescence, with a reversal occurring after the year's longest day (the summer solstice). Across 84% of the northern forest area, increased temperature and vegetation activity before the solstice led to an earlier senescence onset of, on average, 1.9 ± 0.1 days per °C, whereas warmer post-solstice temperatures extended senescence duration by 2.6 ± 0.1 days per °C. The current trajectories toward an earlier onset and slowed progression of senescence affect Northern Hemisphere-wide trends in growing-season length and forest productivity.
Keywords: lesy; klimatické změny; Plant Leaves; teplota; roční období; Climate Change; senescence rostlin; Seasons; Temperature; Forests; Plant Senescence; listy rostlin; ekosystém; Ecosystem